Programmatic and Teaching Initiatives for Ethnically Diverse Nursing Students: A Literature Review - Marivic B. Torregosa, PhD, RN, FNP-BC; Karen H. Morin, DSN, RN, ANEF, FAAN (Elsevier, 2012)
Purpose: The purpose of this study was to examine the evidence of programmatic and teaching initiatives implemented by nursing faculty to enhance the academic success rates of ethnically diverse students (EDS). Methods: A search of the literature in the Cumulative Index to Nursing and Allied Health Literature and MEDLINE databases, wherein primary sources about programmatic and teaching initiative to promote academic success among EDS, was conducted. Using specific the Cumulative Index to Nursing and Allied Health Literature subject headings and Medical Subject Headings, 230 articles were retrieved from both databases. A total of 22 peer-reviewed articles published between 2000 and 2011 were included in the literature review. Results: We found that evidence on the predominant programmatic and teaching initiatives for EDS academic success was inconclusive. The most common programmatic and teaching initiatives implemented by nursing faculty were peer mentoring, faculty-student mentoring, social networking, academic support, and financial support. Conclusion: Although positive student outcomes were reported about programmatic and teaching initiatives for EDS, the evidence remained inconclusive. Recommendations for policy and future research in this area of nursing education research were provided.